Good Governance and Organizational Management - Boonyanunt, Yingyot (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 13 No 1 (2021): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
The articles about Good Governance and Organizational Management focuses on explaining international governance principles, good governance, concepts of good governance in Thailand and the benefits of good governance. The principles of good governance are applied in the management of the organization. There are 6 key principles: Rule of Law, Morality, Accountability, Participation, Responsibility and Cost-Effectiveness or Economy. Good Governance Principles is widely used in corporate management nowadays because it helps to create and promote the organization to have potential and efficiency such as the employees working with honesty and diligence which causing the organization’s performance expand. It also makes third parties have confidence sand faiths in such an organization as well.